2017
DOI: 10.3389/fpls.2017.00461
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Scale Analysis of the PIN Gene Family Reveals Its Functions in Cotton Fiber Development

Abstract: The PIN-FORMED (PIN) protein, the most important polar auxin transporter, plays a critical role in the distribution of auxin and controls multiple biological processes. However, characterizations and functions of this gene family have not been identified in cotton. Here, we identified the PIN family in Gossypium hirsutum, Gossypium arboreum, and Gossypium raimondii. This gene family was divided into seven subgroups. A chromosomal distribution analysis showed that GhPIN genes were evenly distributed in eight ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 57 publications
0
49
0
Order By: Relevance
“…In contrast, BnPIN1b is strongly expressed in the bark. In an analysis of PIN genes in cotton, fiber elongation was observed when the expression of PIN genes was increased [77]. Further research on BnPIN1b may increase our knowledge of the molecular mechanisms underlying bast fiber development in ramie.…”
Section: Analyses Of Tissue-specific Expression Of Bnaux/lax and Bnpimentioning
confidence: 97%
“…In contrast, BnPIN1b is strongly expressed in the bark. In an analysis of PIN genes in cotton, fiber elongation was observed when the expression of PIN genes was increased [77]. Further research on BnPIN1b may increase our knowledge of the molecular mechanisms underlying bast fiber development in ramie.…”
Section: Analyses Of Tissue-specific Expression Of Bnaux/lax and Bnpimentioning
confidence: 97%
“…Two diploid cottons, G. arboreum (AA genome) and G. raimondii (DD genome), evolved from a common ancestor ( Zhang et al, 2017 ). The most widely cultivated tetraploid cotton species are G. hirsutum (AADD, AD1 genome) and G. barbadense (AADD, AD2 genome), both of which originated from inter-genomic hybridization of two A- and D-genome progenitor species ( Paterson et al, 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…While studying the structure of PIN proteins, corresponding functional studies have also been carried out. As an inter-cellular auxin output protein, PIN plays an essential role in the growth and development of plants [4,9,12,20,21,26,40]. There are multiple members in most subgroups of the LcPIN gene family.…”
Section: The Expression Pattern Of Lcpin Gene Was Preliminarily Revealedmentioning
confidence: 99%
“…With the release of genome data for different species, the PIN gene family so far has been identi ed in a variety of living multicellular plants, such as rice, maize, cotton, soybeans, etc. [24][25][26][27]. Transcriptome data analysis and qRT-PCR showed that there might be functional interactions and redundancy between PIN genes, which also play a role in abiotic stress response and interaction with other plant hormones [27,28].…”
Section: Introductionmentioning
confidence: 99%